Implementation of Citizenship Education Learning to Develop a Democratic Culture in Class XII Madrasah Aliyah Pondok Pesantren An-Ni'mah Asahan TA. 2022/2023 - Fadillah, Nur Indah; Lahmuddin, Lahmuddin (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
This research aims to find out how to implement citizenship education learning to develop a democratic culture in class Civic knowledge is one of the subjects that students must understand. This type of research is qualitative research with a descriptive approach, namely data analysis in the form of words, sentences or paragraphs expressed in descriptive form with three stages, namely data reduction, data exposure and decision making so that it can provide an overview of the problem being researched in Class XII Madrasah. Aliyah Islamic Boarding School An-Ni'mah Asahan. In this research, the primary subjects are the class XII Civics Teacher and Researcher, as well as the data collection techniques using observation, interviews and documentation. Thus, it can be concluded that the results of this research show that the level of understanding of Civics teachers in class XII regarding democratic culture can now be said to be much better than before this research was conducted. In this case, teachers are optimal in understanding the concept of democratic culture, the components of democratic culture, types of democratic culture and the values ??of democratic culture. The optimal level of Civics teachers' understanding of democratic culture can have an impact on the Civics teacher's ability to process learning activities that enable students to gain many democratic values. Because basically Civics teachers' understanding of democratic culture will help them in choosing and developing democratic learning strategies so that they can encourage the realization of democratic culture as the ultimate goal of Civics.